A CONGESTIVE HEART FAILURE PADA PASIEN HYPERTENSIVE HEART DISEASE LAPORAN KASUS - Putri Amelia Djamil; Tutik Ernawati (CV. Jasa Sukses Abadi, 2026)
Chronic heart failure is a major cause of morbidity among older adults and is frequently associated with uncontrolled hypertension. This case report aims to describe the management of chronic heart failure in a patient with hypertensive heart disease using a comprehensive family medicine approach. Data were obtained through detailed history taking, physical examination, medical record review, and home visits to assess family dynamics, health behaviors, and environmental factors influencing the patient’s condition. A 65 year old woman presented with progressive dyspnea that worsened during physical activity and when lying down. Her blood pressure was 142 over 95 mmHg, and chest radiography showed cardiomegaly. The patient was diagnosed with chronic heart failure with a history of long standing uncontrolled hypertension. Interventions included pharmacological and non pharmacological strategies consisting of optimization of antihypertensive therapy, low sodium diet education, fluid intake adjustment based on clinical status, structured physical activity recommendations, and active family involvement in monitoring treatment adherence and lifestyle modification. After three weeks of follow up, clinical improvement was observed with blood pressure reduced to 123 over 76 mmHg and a decrease in dyspnea severity measured by the visual analog scale from three to one. The knowledge score of the patient and family increased from 60 percent to 100 percent, accompanied by better medication adherence and routine follow up. A family based comprehensive approach contributed to symptom improvement, enhanced treatment adherence, and better blood pressure control in a patient with chronic heart failure and hypertension.